CO2 and CH4 permeation through zeolitic imidazolate framework (ZIF)-8 membrane synthesized via in situ layer-by-layer growth: an experimental and modeling study - Lai, L.S. (Royal Society of Chemistry, 2015)
In this work, a general model representing the permeation of CO2 and CH4 through Zeolitic Imidazole Framework-8 (ZIF-8) membrane synthesized via in situ layer-by-layer growth under microwave irradiation is developed. The model is formed based on the pressure drop concept in order to predict the intercrystalline properties of the ZIF-8 membrane according to the experimental permeation data of CO2 and CH4. The model combines Knudsen diffusion, viscous flow and generalized Maxwell-Stefan models, which considered the support resistance, gas diffusivity and intercrystalline pores of the membrane layer. The simulated data are fitted well with the experimental gas permeation results and consistent with the physical characterizations, including X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results showed that, layer-by-layer growth managed to reduce the intercrystalline pores present in the ZIF-8 membrane layer, with the approximate pore radius of 2.1 Ã 10-7 m and porosity of 1.15 Ã 10-4. However, the presence of the small pores can significantly affect the performance of the ZIF-8 membrane which resulted in CO2/CH4 ideal selectivity of â¼1. Â© The Royal Society of Chemistry.